2021
DOI: 10.2337/db21-153-lb
|View full text |Cite
|
Sign up to set email alerts
|

153-LB: Initial Presentation of Children with Type 2 Diabetes during the COVID-19 Pandemic

Abstract: Stay at home orders due to the COVID-19 pandemic have exacerbated risk factors for type 2 diabetes. These orders have limited opportunities for daily physical activity, encouraged more screen time and sedentary behaviors, led to disturbed sleep, and promoted consumption of ultra-processed foods. Even modest weight gain over a short period of time can increase the risk for long-term consequences such as type 2 diabetes and cardiovascular disease. During the COVID-19 pandemic, there has been little data on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…However, there was subset of subjects who did have statistically and clinically significant changes in their lipid panel (including increased TC, non-HDL-C, and TG), In these subjects, increases in HgbA1c, fasting insulin, TC, TG, and ALT were indicative of worsening insulin resistance, dyslipidemia, and hepatic steatosis, respectively. These markers, particularly those indicating worsening insulin resistance (increased fasting insulin and HgbA1c), are consistent with reports of higher rates of pediatric type 2 diabetes during the pandemic 17 , 18 , 19 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, there was subset of subjects who did have statistically and clinically significant changes in their lipid panel (including increased TC, non-HDL-C, and TG), In these subjects, increases in HgbA1c, fasting insulin, TC, TG, and ALT were indicative of worsening insulin resistance, dyslipidemia, and hepatic steatosis, respectively. These markers, particularly those indicating worsening insulin resistance (increased fasting insulin and HgbA1c), are consistent with reports of higher rates of pediatric type 2 diabetes during the pandemic 17 , 18 , 19 .…”
Section: Discussionsupporting
confidence: 90%
“…These changes all have the potential to worsen cardiometabolic health. Recent data have demonstrated an increased incidence and severity for new-onset type 2 diabetes 17 , 18 , 19 , an increase in pediatric BMI 20 , 21 , 22 , and worsening exercise capacity 22 , 23 during the pandemic. Furthermore, decreased socioeconomic status from unemployment or underemployment of parents may exacerbate existing disparities including food insecurity and access to care 24 , 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported an increased rate of diabetic ketoacidosis (DKA) and diabetes‐related admissions during the pandemic both for those with type 1 and type 2 diabetes. 7 , 12 , 14 , 16 Our findings may differ for a variety of reasons. Althoush some studied the difference in total number of DKA or hyperglycemic hyperosmolar state events, we looked at the proportion of new diagnoses that presented with acidosis or hyperosmolarity.…”
Section: Discussionmentioning
confidence: 71%
“…1 Reports from other centers do indeed show a rise in cases of type 2 diabetes among youth but show variable results in terms of severity and are focused on the early pandemic period. [12][13][14][15][16][17] The cause of the rise in type 2 diabetes is likely multifaceted. SARS-COV2 is hypothesized to directly increase the risk of hyperglycemia by acting at the angiotensin-converting enzyme 2 receptors expressed in key metabolic organs and tissues, including pancreatic beta cells.…”
Section: Introductionmentioning
confidence: 99%
“…This same group published a quantitative survey which indicated 63% of parents reported a decrease in physical activity, which was exacerbated by a lack of playmates and if there was a lack of availability of adult supervision . Other early studies suggest an increased hospitalization rate for children with Type 2 diabetes during the early pandemic, and an increase in mental health problems among children, as well as the important associations between mental health and health behaviors and overweight/obesity status in children (Hsia et al, 2021;Leff et al, 2021;Alves et al, 2021).…”
mentioning
confidence: 99%